1997
DOI: 10.1007/bf01282129
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyproline-rich glycoprotein mRNA accumulation in maize root cells colonized by an arbuscular mycorrhizal fungus as revealed by in situ hybridization

Abstract: Summary.To determine whether the expression of cell wall related genes changes during the establishment of an arbuscular mycorrhizal symbiosis (AM), we studied the expression of a maize hydroxyproline-rich glycoprotein (HRGP) gene. In situ hybridization showed that, in differentiated ceils of maize roots, mRNA accumulation corresponding to the gene encoding for HRGP was only found when the cells were colonized by the endomycorrhizal fungus Glomus versiforme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 22 publications
3
24
0
3
Order By: Relevance
“…During the later steps of fungal colonization, chitin is ' naked ' and amorphous in the thin branches of arbuscules and can act as a potential source of elicitors. This hypothesis is supported by in situ hybridization experiments which have located transcripts of defence-related genes mainly in arbuscule-containing cells (Harrison & Dixon, 1994 ;Blee & Anderson, 1996 ;Gianinazzi-Pearson et al, 1996 ;Balestrini et al, 1997).…”
Section: Chitin Synthases In Fungal Growth and Morphogenesissupporting
confidence: 61%
“…During the later steps of fungal colonization, chitin is ' naked ' and amorphous in the thin branches of arbuscules and can act as a potential source of elicitors. This hypothesis is supported by in situ hybridization experiments which have located transcripts of defence-related genes mainly in arbuscule-containing cells (Harrison & Dixon, 1994 ;Blee & Anderson, 1996 ;Gianinazzi-Pearson et al, 1996 ;Balestrini et al, 1997).…”
Section: Chitin Synthases In Fungal Growth and Morphogenesissupporting
confidence: 61%
“…A differential expression study provides insight into up-regulation of PM-HRGP transcripts, observed only in resistant cultivars of pearl millet during downy mildew infection Accumulation of HRGP takes place in maize during wounding ), arbuscular mycorrhizal symbiosis (Balestrini et al 1997) and in response to fungal elicitors and infection (Showalter et al 1985). This phenomenon was not observed during wounding in other monocots such as barley, oat, wheat or rice (Mazau and Esquerretugaye 1986;Li and McClure 1990;SommerKnudsen et al 1998).…”
Section: Actamentioning
confidence: 99%
“…Perubahan serangkaian respon fisiologis dan biokimia tanaman dan efek perlindungannya terhadap berbagai cekaman ditentukan oleh derajat/persentase kolonisasi FMA yang dipengaruhi oleh kesesuaian inang-FMA dan lingkungan serta adanya perbedaan morfologi kolonisasi terutama ada/tidaknya arbuskular dan tipe arbuskular (arbuskular spesifik). Peningkatan ketahanan tanaman setelah diinduksi mikoriza berkaitan dengan fase awal perkembangan struktur mikoriza di dalam sel akar tanaman inang yang diawali sejak penetrasi oleh apresorium hingga bentuknya struktur arbuskular (Balestrini et al, 1997). Peningkatan aktivitas enzim peroksidase berhubungan erat dengan perkembangan struktur kolonisasi mikoriza.…”
Section: Pendahuluanunclassified
“…Hasil penelitian Gianinazzi-Pearson & Gianinazzi (1995) (Balestrini et al, 1997;Blee & Anderson, 2000), metabolisme enzim phenylpropanoid (Volpin et al, 1994;Harrison & Dixon, 1993;, enzim yang terlibat dalam metabolisme ROS (reactive oxygen species) (Blee & Anderson, 2000) dan enzim hydrolase (Salzer & Boller, 2000). Ditemukan adanya peningkatan jumlah HRGP mRNA di dalam akar tanaman jagung dan buncis yang mengandung arbuskular (Blee & Anderson, 2000).…”
Section: Pendahuluanunclassified